2021
DOI: 10.1111/eea.13037
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoid‐induced calcium signaling mediates cellular immune responses of Tenebrio molitor

Abstract: Calcium signaling is associated with actin cytoskeleton rearrangement. It is required for expressing cellular immune responses of insect hemocytes. Eicosanoids mediate immune responses by cytoskeleton rearrangement against various pathogen infections in insects. The objective of this study was to investigate cellular immune responses of a mealworm, Tenebrio molitor L. (Coleoptera: Tenebrionidae). The hypothesis tested was that immune responses would be mediated by calcium signaling associated with eicosanoid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The relative proportions of these hemocytes were different, of which GR and PL were the major cell types. The coleopteran Tenebrio molitor larvae possesses at least four morphological types of hemocytes, most of which (almost 75%) are GR and PL (Roy & Kim, 2021). In the lepidopteran insect S. exigua , five hemocyte types have been found and show similar relative compositions as those of A. sapporensis (Park & Kim, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The relative proportions of these hemocytes were different, of which GR and PL were the major cell types. The coleopteran Tenebrio molitor larvae possesses at least four morphological types of hemocytes, most of which (almost 75%) are GR and PL (Roy & Kim, 2021). In the lepidopteran insect S. exigua , five hemocyte types have been found and show similar relative compositions as those of A. sapporensis (Park & Kim, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…, 2018), activates hemocytes, phagocytosis, and the proPO system (Mandato et al. , 1997; Roy & Kim, 2021). In particular, PGE 2 can mediate the occurrence of apoptosis in G. mellonella hemocytes (Wrońska et al.…”
Section: Discussionmentioning
confidence: 99%
“…One eicosanoid action in insect cellular immunity is the activation of Ca 2+ signaling within hemocytes in mealworms, Tenebrio molitor. Roy and Kim (33) reported that bacterial infections stimulate Ca 2+ activation, recorded as Fura-positive cells. One role of Ca 2+ is activating hemocyte spread by F-actin extension, documented by co-localization of Ca 2+ and F-actin.…”
Section: Discussionmentioning
confidence: 99%
“…To observe the Ca 2+ signal and hemocyte aggregation behavior in response to fungal challenges (33), L5 larvae of S. exigua were injected with 2 µL Fura-8 (1 mM) and incubated for 30 min. 2 µL of fungal conidia and hyphae were injected.…”
Section: Ca 2+ Signaling In Response To Fungal Challengementioning
confidence: 99%